Pemanfaatan Serai sebagai Spray Anti Nyamuk oleh Mahasiswa KKNT Bela Negara di Desa Gedangan - I Wayan Darma Batara; Natalia Dwi Wulandari; Roziana Febrianita (Jurnal Kabar Masyarakat, 2024)
Mosquito-borne diseases such as dengue fever, Zika, and malaria pose significant health threats in Indonesia, particularly in tropical areas like Gedangan Village, Jombang Regency. To reduce the risk of disease transmission, students of the Thematic Community Service Program (KKN) from Universitas Pembangunan Nasional "Veteran" Jawa Timur utilized lemongrass (Cymbopogon citratus) as the main ingredient in the production of mosquito repellent spray. This program aims to provide a safer and more environmentally friendly alternative compared to chemical-based products. The training and socialization conducted in Gedangan Village increased the community's understanding of the benefits of lemongrass and how to produce natural mosquito repellent spray. The results of this program show that lemongrass-based spray is effective as a mosquito repellent and can be a long-term solution in reducing dependence on chemical insecticides. The sustainability of this program is expected to be expanded to other villages, with support from the government and related institutions to strengthen its positive impact on public health and the environment.